2020
DOI: 10.3389/fcell.2020.00312
|View full text |Cite
|
Sign up to set email alerts
|

Functional Significance of Satellite DNAs: Insights From Drosophila

Abstract: Since their discovery more than 60 years ago, satellite repeats are still one of the most enigmatic parts of eukaryotic genomes. Being non-coding DNA, satellites were earlier considered to be non-functional "junk," but recently this concept has been extensively revised. Satellite DNA contributes to the essential processes of formation of crucial chromosome structures, heterochromatin establishment, dosage compensation, reproductive isolation, genome stability and development. Genomic abundance of satellites is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 235 publications
(299 reference statements)
0
36
0
1
Order By: Relevance
“…Numerous genome studies have shown the ubiquity and abundance of repetitive elements in plant genomes and have validated the crucial role of repeats in genome structure, function, and evolution (Wicker et al, 2007 ; Shatskikh et al, 2020 ). Once notoriously labeled as “junk DNA,” repetitive elements are now known as important players in gene regulation, stress response, and genome stability (Fedoroff, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous genome studies have shown the ubiquity and abundance of repetitive elements in plant genomes and have validated the crucial role of repeats in genome structure, function, and evolution (Wicker et al, 2007 ; Shatskikh et al, 2020 ). Once notoriously labeled as “junk DNA,” repetitive elements are now known as important players in gene regulation, stress response, and genome stability (Fedoroff, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the common satDNA composition, centromeric and pericentromeric chromatin are structurally different, essentially because centromeres are epigenetically compatible with kinetochore assembly and chromosome segregation, while pericentromeric regions have a typical heterochromatic behavior [ 26 ]. Thus, the ubiquitous centromeric presence of α satellite sequences is contrasted by the nature of pericentromeric satellite families that clearly behave in a more non-homogenous manner [ 23 , 29 , 55 ], frequently leading to incongruences about their overall existence and location in the human genome [ 95 ].…”
Section: Human Satellite Dna Familiesmentioning
confidence: 99%
“…Highly repetitive satellite DNA undoubtedly represents a major gap in human genome assemblies, significantly contributing to the lack of high-resolution sequencing studies in the field of centromere genomics, whose characterization has been substantially hindered by the repetitive nature of satDNA [ 26 , 110 , 111 ]. The availability of computer software algorithms for sequence analysis has been highly restricted to methods excluding repetitive sequences and disregarding their annotation [ 6 , 97 , 111 ].…”
Section: Satellite Dna: Repetitively Challengingmentioning
confidence: 99%
See 2 more Smart Citations